Techno-economic assessment of a hybrid RO-MED desalination plant integrated with a solar CHP system - Jamshidian, Farid Jalili; Gorjian, Shiva; Shafieefar, Mehdi (Energy conversion and management, 2022)
•Proposed solar hybrid desalination system is independent of any fossil-based power source.•Compared to a single multi-effect desalination plant, hybrid system rises total recovery by 15%.•Employing a thermal energy storage unit enhances the working hours by 30%.•About an 8% drop in the final cost of 1 m3 of produced freshwater is observed. In this study, an existing thermal multi-effect distillation (MED) plant was assumed to be integrated with reverse osmosis (RO) desalination system in a way that both heat and electricity demands of the hybrid RO-MED plant could be provided by a solar combined heat and power (CHP) system composed of parabolic trough concentrators (PTCs). For this purpose, the climatic conditions of Bushehr province (latitude 28.7621° N; longitude 51.5150° E), located in the south of Iran, was considered as the case study, and the water demand of 1,000 m3/day was assumed. In the first step, new algorithms were developed to integrate RO and MED desalination plants, and an incorporated thermal energy storage (TES) system was designed using the MATLAB program. Additionally, the whole system including the RO-MED plant and the solar CHP system was mathematically modeled and their performance was technically and economically evaluated. To perform this, four scenarios including recovery values for RO and MED as 50% and 30% (scenario 1), 50% and 35% (scenario 2), 55% and 30% (scenario 3), and 55% and 35% (scenario 4) were deemed. The results revealed that, first of all, the fourth scenario yields the highest total recovery amounts in all considered shares of freshwater production between two desalination plants. Secondly, under this scenario, the optimum total recovery can be obtained when each desalination plant produces 50% of the required freshwater, leading to a 15% rise in total recovery in hybrid mode, compared to the use of a single MED unit. Moreover, it was found that the integration of the TES unit can extend the working hours of the system by 30% under daylight irradiation. From calculations, the number of required PTCs in the solar field was calculated as 188 with a total aperture area of 17,869 m2. The economic evaluation of the designed system illustrated that the integration of a RO plant with an existing MED system could reduce the total cost of the produced freshwater for 6700 people from 2.08 US$/m3 for a single solar-powered MED plant to 1.918 US$/m3 for the solar-powered RO-MED plant.